Power Electronics Handbook. Devices, Circuits, and Applications - Rashid M. H. Muhammad (Burlington, Elsevier, 2011)
KEY FEATURES Strong design, test and troubleshooting element Updated chapter on packaging and smart power systems Updated chapter on fuel-cell power electronics for distributed generation New chapters on renewable energy sources, transmission, and storage New chapter on distributed generation and cogeneration This is an expert guide to total power solutions. Power Electronics Handbook, 3rd Edition, brings together over 100 years of combined experience in the specialist areas of power engineering. Designed to provide the best technical and most commercially viable solutions available, this handbook. undertakes any or all aspects of a project requiring specialist design, installation, commissioning, and maintenance services. The third edition features four new chapters covering energy sources, energy transmission, and energy storage. This edition also includes updated chapters on Fuel-Cell Power Electronics for Distributed Generation, Flexible AC Transmission, Novel Al-Based Soft Computing Applications in Motor Drives, and EMI Effects of Power Converters. With this book in hand, engineers are able to execute design, analysis, and evaluation of assigned projects using sound engineering principles and adhering to the business policies and product/program requirements.